PENGEMBANGAN MODEL PENDIDIKAN KARAKTER EKONOMI MELALUI PEMBELAJARAN BERBASIS OUTCOME BASED EDUCATION PADA MAHASISWA EKONOMI DI KOTA MAKASSAR - Nurjannah; Muhammad Hasan; Andi Tenri Ampa; Irwandi; Elpisah (SEMINAR NASIONAL DIES NATALIS 62, 2023)
The purpose of this study was to develop a model of economic character education through outcome-based education-based learning for economics students in the city of Makassar. This type of research is a quantitative research using Explanatory Research method. The location of this research is at several universities in the city of Makassar. The subjects in this study were students of the Faculty of Economics and Business in Makassar City, while the research object was data on the development of an economic character education model through outcome-based education. Data collection techniques using descriptive methods and survey methods through questionnaires. The analysis technique used is to identify the relationship between variables, test hypotheses, and draw conclusions. Each indicator is thoroughly reviewed using contextual analysis techniques. The results of the study explain that outcome-based education-based learning that is implemented in tertiary institutions, especially in the Faculty of Economics and Business in Makassar City, has various influences in improving the economic character of students through assignments from lecturers by going directly to the field to study economic phenomena that exist in society.